2020
DOI: 10.1186/s12885-020-07702-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a novel glycolysis-related gene signature on progression, prognosis and immune microenvironment of renal cell carcinoma

Abstract: Background Glycolysis is a central metabolic pathway for tumor cells. However, the potential roles of glycolysis-related genes in renal cell carcinoma (RCC) have not been investigated. Methods Seven glycolysis-related gene sets were selected from MSigDB and were analyzed through GSEA. Using TCGA database, the glycolysis-related gene signature was constructed. Prognostic analyses were based on the Kaplan–Meier method. The cBioPortal database was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 67 publications
(73 reference statements)
3
40
0
Order By: Relevance
“…Our results are consistent with previous studies (38). Chong et al found that HMMR was overexpressed in renal cancer and affected the progression, prognosis, and immune microenvironment of renal cell carcinoma (39). Kaplan Meier-Plotter analysis showed that up-regulation of HMMR and enriched in a variety of immune cells correlated with poor prognosis in LUAD.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous studies (38). Chong et al found that HMMR was overexpressed in renal cancer and affected the progression, prognosis, and immune microenvironment of renal cell carcinoma (39). Kaplan Meier-Plotter analysis showed that up-regulation of HMMR and enriched in a variety of immune cells correlated with poor prognosis in LUAD.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous research showed that glycolysis was markedly enriched in RCC tissues compared with normal tissues because it supplies basic carbon units for DNA replication, induces therapeutic resistance in tumor cells, and maintains a high ratio of ATP/ ADP for proliferation. 45 However, glycolysis enrichment was not affected by SLC7A11 expression, which may result from metabolic plasticity caused by SLC7A11. 44,46 In summary, SLC7A11 has a complicated and profound impact on RCC metabolism.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, several bioinformatics analyses have reported that these genes (HMMR, KIF20A, PGM2L1, ANKZF1, and GPR87) participate in glycolysis ( 51 , 52 ). However, their roles in regulating tumor glycolysis have rarely been confirmed.…”
Section: Discussionmentioning
confidence: 99%